Consumer Protection in Expired Food Cases - Sumito, Sumito; Saputra, Rio; Darmawan, Didit; Wibowo, Agung Satryo; Hardyansah, Rommy (Bulletin of Science, Technology and Society, 2024)
Expired food is a serious problem that threatens public health and violates consumer rights. This research explores the challenges in implementing consumer protection regulations against the circulation of expired food in Indonesia. Using a normative juridical approach, this study analyzes existing regulations, barriers to their implementation, and factors that influence the effectiveness of legal protection. The results show that weak supervision, low consumer literacy, and lack of coordination across sectors are the main obstacles. Strategic recommendations include strengthening regulations, increasing the capacity of supervisory institutions, consumer education, utilizing technology, applying strict sanctions, and cross-sector collaboration. These strategies are expected to improve consumer legal protection in a sustainable manner, creating a safer and fairer market.